The Proapoptotic Effect of Formononetin in Human Osteosarcoma Cells: Involvement of Inactivation of ERK and Akt Pathways - Yun Liu; JinJie He; XiaoMing Chen; Jian Li; MaoRong Shen; WenJun Yu; Yuan Yang; ZengMing Xiao (Cellular Physiology and Biochemistry, 2014)
Background: Previous studies have shown that some phytoestrogens inhibits proliferation and induces apoptosis in estrogen-dependent cancers via estrogen receptor (ER)-mediated signaling pathway. In view of the expression of ER in human osteosarcoma cells, the purpose of this study is to investigate whether formononetin and calycosin, two of the major isoflavones in Radix astragali, could also elicit anti-tumor activity against osteosarcoma, along with the underlying mechanism. Methods: Human osteosarcoma cells U2OS were respectively treated with various concentrations of formononetin or calycosin. Cell proliferation was determined by MTT assay, while apoptosis by flow cytometry. Next, the expression levels of apoptosis-related genes ERK, Akt, Bcl-2, Bax and caspase-3 were quantified by real-time PCR and Western blotting. Results: Formononetin exhibited higher anti-proliferative activities toward human osteosarcoma cells U2OS, when compared with calycosin. Therefore, U2OS cells were then respectively treated with various concentrations of formononetin, in order to elucidate the isoflavones-related signaling pathway. It was found that formononetin dose-dependently triggered apoptosis of U2OS cells in vitro. Furthermore, treatment of formononetin led to significant inactivation of ERK and Akt, followed by downregulation of Bcl-2, upregulation of Bax and finally increased expression of caspase-3. Conclusion: Formononetin is more effective than calycosin at promoting cell death of U2OS cells by induction of apoptosis, which is mediated by inactivation of ERK and Akt signaling pathways. Thus isoflavones, especially formononetin, may be useful as anti-cancer drugs for osteosarcoma through their apoptosis-inducing effects.